Kajian Jumlah Biji Basah dan Berat Bji Basah Kopi Robusta (Coffea robusta Lindl.)Pada Beberapa Ketinggian, Kemiringan Lereng dan Jenis Tanah di Kecamatan Silima Pungga-Pungga Kabupaten Dairi - Syahputra Abadi Sembiring; posma marbun; kemala sari lubis (Universitas Sumatera Utara, 2016)
The purpose of reviewing robusta coffee (Coffea robusta Lindl.) production at some height, slope, and soil type in Silima Pungga-Pungga regency of Dairi. After overlaying map of ground tipe, elvation, and slope it was found 18 SPT (set of land) with the scale 1 : 25.000. The population of the research is coffee tree in the study field. Sum of point of sampling for coffee trees are 540 sample points. The result of data analysis showed the higest sum of ripe seed coffee production at Great Group Hydrudands as SPL (set of land) 12 and the lowest sum of ripe seed coffee production at Great Group Kadiudults as SPL 1. The highest weight production of ripe seed coffee production at Great Group Hydrudands as SPl (set of land) 12 and the lowest weight production of ripe seed coffee production at Great Group Kadiudults as SPL 1. Keywords : height, slope, soil type, coffee production